PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) TERHADAP HASIL BELAJAR FISIKA PADA MATERI USAHA (KERJA) DAN ENERGI BAGI SMAN 1 PLAKAT TINGGI - Lilis Juarsih; Abidin Pasaribu; Sardianto Markos Siahaan (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
This study aims to describe the influence of the Problem Based Learning (PBL) model on the learning outcomes of physic subject in case of the material of Effort and Energy for Students SMAN 1 Plakat Tinggi. This study was conducted in the even semester of the academic year 2016/2017. The research method used in this research is Quasy Experimental, with design Non - Equivalent Control Group Design. The population in this study is the entire students of class X SMA Negeri 1 Plakat Tinggi. The sample of this research is class X IPA1 as an experimental class and class X IPA2 as the control class. The sample of this research is selected with technique of Purposive Sampling. Learning process at the experimental class gets treated with the Problem Based Learning model and in the control class is taught with the Conventional Learning model. The data collection used a multiple choice questionnaire test technique consisting of 24 questions consisting of 12 pretest questions and 12 posttest questions, to measure student learning outcomes on cognitive aspects. Based on the hypothesis test using t-test on the level of significance (α) = 5%, obtained price t arithmetic = 8.994 and t table = 1.991 seen that t count > t table.. Therefore, H0 is rejected and Ha is accepted. It can be concluded that there is an influence from the use of problem-based learning model on learning outcomes of Physic Class X SMAN 1 Plakat Tinggi.